Recurrent uncomplicated urinary tract infections: definitions and risk factors - Cai, Tommaso (GMS Infect Dis, 2021)
Introduction: Recurrent uncomplicated urinary tract infections (UTI) have a high impact on patients’ quality of life and high direct and indirect costs for public health. Therefore, optimal management should be of high priority. Methods: Current international guidelines were reviewed, and a systematic literature search was performed in Medline, Cochrane, and Embase. Results: Several risks factors have been identified and used in everyday clinical practice to plan the correct strategy for recurrence prevention. Among all factors, the most important are: sexual intercourse, spermicide use, having a new sex partner, having a mother with a history of UTI, having had UTI during childhood, and asymptomatic bacteriuria treatment. Moreover, other risk factors such as reduced fluid intake, habitual and post-coital delayed urination, wiping from back to front after defecation, douching and wearing occlusive underwear, as well as irregular bowel function should be taken into account. Conclusions: Recurrent UTI show a high impact on clinical practice. Risk factors are generally related to both virulence of pathogens and patient’s behavior or condition. A recently developed nomogram can assist in identifying women at high risk of symptomatic recurrence that can be suitable candidates for a prophylactic strategy.